Sila Kelima Pancasila Sebagai Landasan Penegakan Hukum: Upaya Membangun Sistem Perdagangan Yang Adil dan Berkelanjutan - Ramadhani, Kalya Sukma; Shafwah, Salsabila; Lovita; Artha, Widya; Hartanto, Adrian; Tumanggor, Raja Oloan (Universitas Tabanan, 2024)
The increasing popularity of affordable products has led to high demand among many people, including branded goods, electronic devices and others that are easily purchased through illegal market distributors. Various types of products sold at lower prices, but with “big” brands are common on the black market, but consumers are often unaware of the dangerous consequences of purchasing illegal products. Therefore, it is important to have equal implementation of the law in accordance with the fifth principle of Pancasila. The purpose of this study was to determine the understanding and appreciation of the community, especially from the perspective of Generation Z and the general public, towards justice in the application of laws related to the black market in Indonesia. The research approach used was qualitative descriptive through interviews with 11 participants. The research findings show that the application of justice in law enforcement in Indonesia is still lacking. Most participants gave negative opinions regarding the law enforcement system related to the black market, arguing that law enforcement has not been implemented optimally and is often unfair, especially in relation to major violators who often avoid punishment. This analysis confirms that the application of the law in handling the black market does not fully represent the principle of social justice required by Pancasila.